Neither our relationship with God nor our formation would be Ignatian... (Journal of Parents and Teachers, 2026)
To move beyond teaching that relies solely on textbooks and the teacher, this school uses videos as a teaching resource. This approach is divided into three distinct levels: video as a support tool, video as a means of expression, and video as a tool for analysis. This new approach to education has been shown to improve oral and written expression, as well as fostering teamwork.
Keywords: Education; Video; Active learning; Recording